Impact of Corporate Social Responsibility to Firms' Performance in Southern Enterprises of Vietnam - Tiep, Le Thanh; Huan, Ngo Quang; Hong, Tran Thi Thuy (International Review of Management and Marketing, 2020)
This study is aimed to evaluate the impact of corporate social responsibility (CSR) on firms' performance by developing the role of mediating variables such as corporate reputation (CR) and customers' purchasing intention (CPI). We use qualitative and quantitative technique such as Smart PLS SEM to analyze the data of the corporate in the South of Vietnam in 2019. The findings suggest a positively significant impact of corporate social responsibility on firms' performance through mediating role of CR and CPI. This study contributed empirical work in the literature of corporate social responsibility and firms' performance. The outcomes of this study can be used by entrepreneurs, top management as an attempt to boost the performance of the corporate. A mediating role of corporate reputation (CR) and customers' purchasing intention (CPI) as a value-added contribution to this study and can be strengthened more in future research. Keywords: Corporate Social Responsibility, Corporate Reputation, Purchasing Intention; Firms' Performance. JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.9900